2019
DOI: 10.1080/14680629.2019.1643769
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a sustainable asphalt mix incorporating high RAP content and novel bio-derived binder

Abstract: The recent drive to find ways to increase sustainability and decrease costs in asphalt paving has led researchers to find innovative ways to incorporate more recycled materials and bioderived binders into mixes with varying success. A new novel bio-derived binder made from refined pine chemistry stabilized with a polymer can increase the sustainability of asphalt mixes while maintaining pavement performance. Laboratory performance testing was conducted on asphalt mixes containing 50% Reclaimed Asphalt Pavement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Cellulose and hemicellulose are polysaccharides that are readily converted into fuels and chemicals, such as hydroxymethylfurfural or sugar alcohols such as xylitol, through straightforward acid catalysis (5,10), while lignin is a complex aromatic polymer network whose valorization is challenging because of its inherent recalcitrance (1,5). Presently, lignin is separated from biomass at a rate of approximately 70 to 100 million metric tons/year through pulping or biorefining processes (11,12), but most isolated lignins have a dark color, strong odor, broad molecular weight distribution, and limited reactivity (5,(13)(14)(15), which restricts them to low-value applications (e.g., fillers for tires, asphalt, or concrete) (16,17). Furthermore, there is substantial variability in the composition, chemical structure, cost, and environmental impact of technical lignins due to differences among feedstocks and pulping/refining techniques (13,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose and hemicellulose are polysaccharides that are readily converted into fuels and chemicals, such as hydroxymethylfurfural or sugar alcohols such as xylitol, through straightforward acid catalysis (5,10), while lignin is a complex aromatic polymer network whose valorization is challenging because of its inherent recalcitrance (1,5). Presently, lignin is separated from biomass at a rate of approximately 70 to 100 million metric tons/year through pulping or biorefining processes (11,12), but most isolated lignins have a dark color, strong odor, broad molecular weight distribution, and limited reactivity (5,(13)(14)(15), which restricts them to low-value applications (e.g., fillers for tires, asphalt, or concrete) (16,17). Furthermore, there is substantial variability in the composition, chemical structure, cost, and environmental impact of technical lignins due to differences among feedstocks and pulping/refining techniques (13,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…50% RA) could be incorporated into asphalt mixtures with suitable biobinders, restoring their rheological properties and enhancing the performance of the mixture [116][117][118][119][120]. Such bio-derived mixtures with RA can sufficiently pass the design requirements for pavements and perform well at low, intermediate and high temperatures without the need of neat bitumen [121]. Table 6 summarises the results of the recycled asphalt and biobinder studies found.…”
Section: Biobinder and Recycled Asphalt Studiesmentioning
confidence: 99%
“…Meanwhile, Baqersad and Ali (2021) [ 29 ] have investigated the use of a nanomodified asphalt binder in the recycling of RAP material to increase the incorporation of RAP percentages in recycled asphalt. In general, there are many different studies on the use of rejuvenators for the homogenization of asphalt mixtures with RAP [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%